2020
DOI: 10.31949/jb.v1i4.493
|View full text |Cite
|
Sign up to set email alerts
|

Pelatihan Bahasa Inggris Berbasis Daring Dengan Konsep Mentoring Dan Tutor Teman Sebaya

Abstract: The globalization and disruption era creates effects for the human being; one is the connection between people without boundaries. This thing also brings up the importance of English language usage. This community service was conducted through online English training, which consists of 8 meetings between June-July 2020. The training includes 1 mentor and 3 participants. The initial assessment was conducted to know the participants’ abilities and categorize them into Basic, Intermediate, Advanced classes. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…This could instil the students to dream high and find funding opportunities. Several community service programmes facilitated participants to know various funding opportunities for pursuing higher studies (Aini et al, 2022;Maharani, 2021;Susanti & Zumrudiana, 2022). It suggested that even if the students in the present community service programme were from financially struggling families, this should not hinder their dream to pursue their study and their dreams.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This could instil the students to dream high and find funding opportunities. Several community service programmes facilitated participants to know various funding opportunities for pursuing higher studies (Aini et al, 2022;Maharani, 2021;Susanti & Zumrudiana, 2022). It suggested that even if the students in the present community service programme were from financially struggling families, this should not hinder their dream to pursue their study and their dreams.…”
Section: Resultsmentioning
confidence: 98%
“…Nonetheless, the particular programme aiming at increasing student motivation to pursue higher education may be one of a kind. Some community service programmes have aimed to make their participants aware of the importance of education and pursuing higher education (Aini et al, 2022;Maharani, 2021;Maskar & Wulantina, 2019;Susanti & Zumrudiana, 2022). For example, a community service activity by Maskar and Wulantina (2019) was conducted to facilitate the residents of Hanura village on possible cooperation and opportunities to pursue further studies.…”
Section: Introductionmentioning
confidence: 99%
“…Langkah-langkah tersebut dapat membantu pelamar beasiswa agar dapat menulis esai yang memberikan kesan kuat dan dapat meyakinkan pihak pemberi beasiswa. (Maharani, 2021).…”
Section: Hasil Pembahasanunclassified
“…majunya teknologi, komunikasi dapat dilakukan dalam jarak jauh tanpa harus bertatap muka. Mempelajari bahasa asing salah satunya bahasa Inggris sangat bermanfaat untuk berkomunikasi dengan orang asing (Andika, 2023). Bahasa Inggris merupakan bahasa internasional utama dan bahasa umum semua negara di dunia, sehingga jika kita ingin memasuki kancah internasional maka kita harus menguasai bahasa tersebut (Chairina, 2019).…”
unclassified